AKIBAT HUKUM TIDAK DILAKSANAKAN PUTUSAN HAKIM PENGADILAN TATA USAHA NEGARA - Hulu, Klaudius Ilkam; Telaumbanua, Dalinama; Laia, Fianusman (LPPM Universitas Nias Raya, 2024)
The fulfillment of the element of utility in a judge's ruling is achieved through execution, ensuring that justice for the parties involved is not merely inscribed on paper, as paper is merely a tool, while justice must be felt. This study aims to understand, comprehend, and analyze the legal consequences of the non-execution of administrative court rulings. The type of research employed is normative legal research, utilizing a statutory approach and an analytical approach, with data collection techniques involving literature study through the analysis of secondary data. Based on the findings and discussions, it can be concluded that the legal consequence of not executing an administrative court ruling is the imposition of sanctions as stipulated in Article 116 of Law No. 51 of 2009 concerning Administrative Courts, in the form of the payment of coercive fines and administrative sanctions. Dwangsom or coercive fines refer to the payment of a certain amount of money, either in a lump sum or in installments, to the individual or their heirs, or to a private legal entity, which is charged to the defendant (a State Administrative Body or Official) for failing to execute an Administrative Court ruling that has permanent legal force (inkracht van gewijsde) and which causes material losses to an individual or private legal entity. In such cases, sanctions in the form of compensation and rehabilitation may be imposed. In administrative court proceedings, the obligation to pay compensation and the imposition of compensation may result in enforcement actions, such as execution, if the losing party fails to comply with or neglects to implement the court's ruling. This action is carried out by the state through court officials upon the request of the winning party in the ruling.